2008
DOI: 10.1021/jf800780f
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal Activity of Plant Essential Oils and Components from Coriander (Coriandrum sativum), Oriental Sweetgum (Liquidambar orientalis), and Valerian (Valeriana wallichii) Essential Oils against Pine Wood Nematode (Bursaphelenchus xylophilus)

Abstract: Commercial essential oils from 28 plant species were tested for their nematicidal activities against the pine wood nematode, Bursaphelenchus xylophilus. Good nematicidal activity against B. xylophilus was achieved with essential oils of coriander (Coriandrum sativum), Oriental sweetgum (Liquidambar orientalis), and valerian (Valeriana wallichii). Analysis by gas chromatography-mass spectrometry led to the identification of 26, 11, and 4 major compounds from coriander (Coriandrum sativum), Oriental sweetgum (Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 14 publications
3
93
0
2
Order By: Relevance
“…This is of particular interest in phytoparasitic nematode control since complex disease symptoms are also commonly associated with accompanying pathogenic microbiota (Back et al, 2002;Vicente et al, 2011). Several EOs, such as those of Cinnamomum zeylanicum (Kong et al, 2006); Boswellia carterii, Paeonia moutan, Perilla frutescens, Schizonepeta tenuifolia (Choi et al, 2007a); Thymus vulgaris (Kong et al, 2007); Litsea cubeba, Pimenta dioica, Trachyspermum ammi ; Coriandrum sativum and Liquidambar orientalis (Kim et al, 2008) have revealed strong activities against B. xylophilus.…”
Section: Introductionmentioning
confidence: 99%
“…This is of particular interest in phytoparasitic nematode control since complex disease symptoms are also commonly associated with accompanying pathogenic microbiota (Back et al, 2002;Vicente et al, 2011). Several EOs, such as those of Cinnamomum zeylanicum (Kong et al, 2006); Boswellia carterii, Paeonia moutan, Perilla frutescens, Schizonepeta tenuifolia (Choi et al, 2007a); Thymus vulgaris (Kong et al, 2007); Litsea cubeba, Pimenta dioica, Trachyspermum ammi ; Coriandrum sativum and Liquidambar orientalis (Kim et al, 2008) have revealed strong activities against B. xylophilus.…”
Section: Introductionmentioning
confidence: 99%
“…Many components were characterized, but the major ones were terpinen-4-ol, α-terpinol, sabinene and γ -terpinene. Up to date, several researchers reported that storax also has protective activity on many bacteria species, phytopathogenic fungi and nematode (Sagdic et al, 2005;Oskay and Sarı, 2007;Kim and Seo, 2008; Lee et al, 2009;Bayramoğlu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A. zerumbet, from the Zingiberaceae family, exhibits antioxidant (ELZAAWELY et al, 2007), antibacterial and antifungal activities (VICTÓRIO et al, 2009). C. sativum, belonging to the Umbelliferae family, has antifungal activity (FURLETTI et al, 2011), nematicidal activity against the phytonematode Bursaphelenchus xylophilus (KIM et al, 2008), and anthelmintic activity on gastrointestinal nematodes (EGUALE et al, 2007).…”
Section: Introductionmentioning
confidence: 99%